Kontribusi Teknologi, Modal, dan Keterampilan Petani Terhadap Produktivitas Bawang Merah - Fajar, Abd; Ayyub Ht, A. Muh.; Indriani, Indriani; Said, Sadly ashari (Hasanuddin University, 2025)
Suboptimal agricultural performance highlights the need to investigate the roles of technology adoption, capital accessibility, and farmers’ skills in improving farm productivity. This study aimed to assess the extent to which these three variables influence the productivity of shallot farms in Bungin Subdistrict, Enrekang Regency. Conducted in February 2025, this research employed a quantitative approach using survey methods for data collection. Structured questionnaires were administered to 60 randomly selected farmers. The data were analyzed using multiple linear regression preceded by classical assumption testing to ensure the model’s validity. The results demonstrate that technology adoption, capital, and farmer skills have a statistically significant simultaneous effect on productivity. Partially, technology adoption shows a positive and significant influence, whereas capital and farmer skills exhibit a significant negative effect. The coefficient of determination (R²) of 0.378 suggests that these variables moderately explain the variations in productivity. These findings underscore the importance of effective implementation and management of production factors at the farm level. Thus, agricultural policy interventions that support technological accessibility, efficient capital allocation, and capacity building among farmers are essential for enhancing sustainable agricultural productivity